PENGARUH SIZE, PROFITABILITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Sumaryono, Ani; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study is aimed to examine the influence of Size (firm size), profitability (ROA) and leverage (DER) to the corporate social responsibility disclosure in the consumer goods industry companies which are listed in Indonesia Stock Exchange. The samples have been selected by using purposive sampling method. The population is all consumer goods industry companies which are listed in Indonesia Stock Exchange in 2012-2015 periods. The population is 33 consumer goods industry companies and 21 consumer goods industry companies with 4 years observation sample in 2012-2015 periods have been selected as samples. The analysis method has been carried out by using multiple linear regression analysis and the SPSS (Statistical Product and Service Solution). The result of there search indicates that size give positive and significant influence to the corporate social responsibility disclosure with its regression coefficient is 6.974 and its significant level is 0.000, profitability does not give any influence to the corporate social responsibility disclosure with its regression coefficient is 0.765 and its significant level is 0.447, leverage give positive influence to the corporate social responsibility disclosure with its regression coefficient is 2.501 and its significant level is 0.014. It has been found from the determination coefficient (R2) that the R square value is 0.441, or 44.1%, which means the ability of size, profitability and leverage in explaining corporate social responsibility disclosure variable as the dependent variable is still low.Keywords: Size, profitability, leverage, corporate social responsibility.